Well-being Marketing: An Ethical Business Philosophy for Consumer Goods Firms - Sirgy, M. Joseph (Journal of business ethics, 2008)
In this article we build on the program of research in well-being marketing by further conceptualizing and refining the conceptual domain of the concept of consumer well-being (CWB). We then argue that well-being marketing is a business philosophy grounded in business ethics. We show how this philosophy is an ethical extension of relationship marketing (stakeholder theory in business ethics) and is superior to transactional marketing (a business philosophy grounded in the principles of consumer sovereignty). Additionally, we argue that well-being marketing is based on duty ethics concepts, specifically the duty of beneficence and non-maleficence. Subsequently, we show how the well-being concept guides marketing decisions for consumer goods firms.